PERBANDINGAN PENGGUNAAN DISFEMIA PADA JUDUL BERITA TERKINI NASIONAL DI TV ONE DENGAN PAWARTOS NGAYOGYAKARTA DI JOGJA TV - Budiawan, R. Yusuf Sidiq (SASINDO, 2014)
The research on the use of dysphemisms aims at 1) describing the forms of dysphemisms used in headlines in Indonesian language on TV One and Javanese on Jogja TV, 2) describing the sense of value in the dysphemisms used, 3) describing the news topics that gave rise the dysphemisms, and 4) describing the linguistic characteristics. It is descriptive-qualitative research supported by the data which was collected by using notes and purposive sampling techniques (Mastoyo, 2007: 44-46). The techniques will record the observations of The Latest headlines news that potentially had the dysphemisms taken from the national news on TV One and Pawartos Ngayogyakarta news on Jogja TV. The data was analyzed by performing a triangulation technique (Elliott, 1991: 82) through three perspectives. In addition, the data is presented with formal and informal methods. The findings show that 1) The dysphemisms are only used at the level of words, 2) the sense of value in the headlines on TV One can be classified into five types, while the sense of value in the headlines on Jogja TV can only be classified into two types, 3) the dysphemisms on TV One showed up in 5 news topics, whereas in the news on Jogja TV was found in 3 kinds of topics, 4) the use of dysphemisms on TV One are more highlighted and offensively "attack" the direct object preached, while on Jogja TV are not.Keywords : Dysphemism, sense of value, headline news, TV One, Jogja TV, Berita